Accounts Receivable Turnover Analysis In Increasing Net Profit At PT. (Persero) Indonesia Credit Protection Medan Branch - Pandapotan Ritonga (AIBPM Publisher, 2022)
The research conducted by the author aims to determine and describe the decline that occurred from the level of receivables turnover, and how the level of receivables turnover in increasing net income at PT. (Persero) Indonesian Credit Insurance which analyzed the company's financial statements. This type of research is descriptive qualitative, with the object of research seen from the financial statements of PT. (Persero) Indonesia Credit Insurance Medan Branch. Where in this study was conducted by analyzing the amount of the company's receivables, and also from the level of the company's net income. The results showed that the decline in receivables turnover was due to the increasing number of company receivables each year. Likewise, the company's net profit also decreased, which was due to a decrease in the company's income, as well as an increase in the company's expenses. Meanwhile, the decline in receivables turnover has a negative impact on the company's net profit.Keywords: Accounts Receivable Turnover and Net Profit.